2017
DOI: 10.1002/2016wr019502
|View full text |Cite
|
Sign up to set email alerts
|

Early formation of preferential flow in a homogeneous snowpack observed by micro‐CT

Abstract: We performed X‐ray microtomographic observations of wet‐snow metamorphism during controlled continuous melting and melt‐freeze events in the laboratory. Three blocks of snow were sieved into boxes and subjected to cyclic, superficial heating or heating‐cooling to reproduce vertical water infiltration patterns in snow similarly to natural conditions. Periodically, samples were taken at different heights and scanned. Results suggest that wet‐snow metamorphism dynamics are highly heterogeneous even in an initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 68 publications
(122 reference statements)
6
36
0
Order By: Relevance
“…Also, the diameter of samples was consistent with the thickness of similar experiments in soils (see e.g. Hill and Parlange, 1972), whereas Avanzi et al (2017a) showed that preferential flow may be intrinsically coupled with wet snow metamorphism at grain scale. This suggests that small-scale experiments are appropriate for understanding the physics of this process in snow.…”
Section: Water Percolation Through Preferential Flow Paths and Capillsupporting
confidence: 80%
See 1 more Smart Citation
“…Also, the diameter of samples was consistent with the thickness of similar experiments in soils (see e.g. Hill and Parlange, 1972), whereas Avanzi et al (2017a) showed that preferential flow may be intrinsically coupled with wet snow metamorphism at grain scale. This suggests that small-scale experiments are appropriate for understanding the physics of this process in snow.…”
Section: Water Percolation Through Preferential Flow Paths and Capillsupporting
confidence: 80%
“…This simplified condition for infiltration into dry snow may lead to an underestimation of the expansion of preferential flow. Neglecting quick metamorphism in preferential flow paths (Avanzi et al, 2017a) may represent another cause of underestimation of preferential flow path size as grain growth promotes lateral spreading of water and expansion of paths. Although this model includes grain growth following Brun et al (1989) and Tusima (1978), modelling some specific conditions such as wet snow metamorphism at the boundaries between preferential flow paths and drier snow is still an open issue.…”
Section: Wet Snow Ratio and Preferential Flow Path Areamentioning
confidence: 99%
“…The cold‐laboratory experiment considered in this paper includes micro‐CT observations of wet‐snow metamorphism in a nature‐identical snow sample (Schleef et al, ) that was subjected to periodical melt cycles with no refreezing (see Figure S1 in the supporting information for the schedule of melt cycles and the estimated height of the snow sample throughout the experiment). More details about this experiment are reported in Avanzi et al () as Experiment M2. We replicated this experiment using a multidimensional water transport model (Hirashima et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…Even though models for wet snow metamorphism have been developed based of experiments on real snow samples (Brun et al, ), these models have rarely been validated for natural snowpacks (Hirashima et al, ), and their accuracy and impact on liquid water flow processes through snow remain largely unknown. Here, we first validate wet‐snow metamorphism patterns derived using a widely used parametrization of wet‐snow metamorphism (Brun et al, ) against observations from a cold‐laboratory experiment that was representative of seasonal snow (Avanzi et al, ). We then use the comparison between model simulations and observations to investigate the role that grain‐growth rates play in ruling the evolution of water flow regimes with time and in particular the transition from preferential flow to matrix flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation